The return of the rentier. Review of 'Capital in the 21st century' by Thomas Piketty - Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2014)
Book review of: Piketty, Thomas (2014): Capital in the 21st century. Harvard University Press, 685 pages
Keywords: 330